2010
DOI: 10.1146/annurev-lawsocsci-102209-152851
|View full text |Cite
|
Sign up to set email alerts
|

Law and Society: Project and Practice

Abstract: This review analyzes four decades of law-and-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
1
27
0
4
Order By: Relevance
“…But the presumption that legal policy is translated into practice in a uniform and orthodox manner is belied by a long line of law and society scholarship. Indeed, the question of whether there is a gap between "law on the books" and "law in action" has long ago been asked and answered (Abel 2010); more fruitful questions interrogate the specificities of translating formal law into practice. In the context of criminal courts, now-classic scholarship has demonstrated the impact of proximate and distal contexts on how cases are adjudicated (see Ulmer 2012 for a full review).…”
Section: Sentencing In Practicementioning
confidence: 99%
“…But the presumption that legal policy is translated into practice in a uniform and orthodox manner is belied by a long line of law and society scholarship. Indeed, the question of whether there is a gap between "law on the books" and "law in action" has long ago been asked and answered (Abel 2010); more fruitful questions interrogate the specificities of translating formal law into practice. In the context of criminal courts, now-classic scholarship has demonstrated the impact of proximate and distal contexts on how cases are adjudicated (see Ulmer 2012 for a full review).…”
Section: Sentencing In Practicementioning
confidence: 99%
“…He qualitatively tracked the tendency during the first 13 years to study the impacts of law on social behavior and the behavior of legal institutions, such as courts and police. In the last 13 years, he detected a cultural turn towards legal narrativity, an inequality turn toward legal mobilization by subordinated groups, and a legal pluralism turn (Abel : 13). Silbey and Abel piqued my curiosity about how LSR authors over the years positioned law vis‐à‐vis society, and what this tells us about how the field, through the journal, has conceptualized law and society .…”
Section: Change Disguised As Continuity In Studying Law and Society? mentioning
confidence: 99%
“…Answering that requires certain spontaneity." 10 [Field notes, interview with a chair judge, October 25, 2010] More than 50 years ago, legal sociologists close to the Law and Society movement (see Abel 2010) clearly demonstrated that not all judges judge in the same way. The different attitudes of the court adjudicators in dealing with cases were, therefore, neither a novelty nor an exception.…”
Section: Embarrassing Intimaciesmentioning
confidence: 99%